MagiCS solving magic squares using clonal selection and simulated annealing - Ojacastro, Maria Fe M.; Regis, Kristine C. (Tacloban City Maria Fe M. Ojacastro, 2009)
The Magic Square construction problem provides an excellent means to develop computer techniques for manipulation of arbitrary digits and number pattern identification. This study proposes a method in solving such problem by using a hybrid algorithm that consists of an immune-inspired algorithm, CLONALG, and the Simulated Annealing algorithm. Given the strengths of these algorithms, experiment results showed that indeed, the proposed hybrid algorithm does solve the Magic Square problem effectively.
Undergraduate thesis (B.S. Computer Science)--University of the Philippines, Tacloban.
Keywords: Magic Squares; Puzzles; CLONALG; Simulated Annealing; Artificial Immune System